1234567891011121314151617181920212223242526272829303132 |
- % ruletest5.al
- VARIABLES X', Y'
- E1 = (X+Y)^2 + (X-Y)^3
- E2 = (X-Y)^2
- E3 = X^2 + Y^2 + 2*X*Y
- M1 = [E1;E2]
- M2 = [(X+Y)^2,(X-Y)^2]
- M3 = M1 + [X;Y]
- AM = EXPAND(M1)
- CM = EXPAND([(X+Y)^2,(X-Y)^2])
- EM = EXPAND(M1 + [X;Y])
- F = EXPAND(E1)
- G = EXPAND(E2)
- A = FACTOR(E3, X)
- BM = FACTOR(M1, X)
- CM = FACTOR(M1 + [X;Y], X)
- A = D(E3, X)
- B = D(E3, Y)
- CM = D(M2, X)
- DM = D(M1 + [X;Y], X)
- FRAMES A, B
- A_B = [1,0,0;1,0,0;1,0,0]
- V1> = X*A1> + Y*A2> + X*Y*A3>
- E> = D(V1>, X, B)
- FM = DT(M1)
- GM = DT([(X+Y)^2,(X-Y)^2])
- H> = DT(V1>, B)
|